2017
DOI: 10.1038/s41598-017-16160-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of intimal hyperplasia in murine aortic allografts by administration of a small-molecule TLR4 inhibitor TAK-242

Abstract: Graft arteriosclerosis (GA) is the leading cause of late cardiac allograft dysfunction. The innate immune system plays a major role in GA, paprticularly Toll-like receptor 4 (TLR4) signaling. Here we characterized the role of TLR4 and its antagonist TAK-242 in a mouse model of GA. BALB/c (H-2d) donor aortas were transplanted into C57BL/6 (H-2b) recipients, and the mice received intraperitoneal injection of 3 or 10 mg/kg of TAK-242 or vehicle every other day for 1, 2, 4, 6, 8 and 12 weeks. With TAK-242 administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…Previous studies by others also showed that the inhibition of TLR-4 led to the inhibition of LPS [20] and megalo-type α-1,6-glucosaccharideinduced NO production [21]. TLR-4 inhibition also decreased immunoexpression of iNOS in the microglia of day old Wistar rats [22] and allografts [23]. It is of note that in this study iNOS expression was significant even in the un-stimulated group, which was contrary to our expectations.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies by others also showed that the inhibition of TLR-4 led to the inhibition of LPS [20] and megalo-type α-1,6-glucosaccharideinduced NO production [21]. TLR-4 inhibition also decreased immunoexpression of iNOS in the microglia of day old Wistar rats [22] and allografts [23]. It is of note that in this study iNOS expression was significant even in the un-stimulated group, which was contrary to our expectations.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, TAK-242 may be a promising drug for the treatment of inflammatory diseases involving TLR4, such as sepsis [ 21 ]. In addition to being able to relieve acute kidney injury, TAK-242 can ameliorate inflammatory injury in cerebral hemorrhage and acute cerebral ischemia/reperfusion, and can also inhibit intimal hyperplasia in murine aortic allografts [ 22 25 ]. In addition, TLR4 promotes the production of inflammatory cytokines through MyD88- and TRIF-dependent pathways [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…HMGB1 has two receptors, i.e., TLR4 and RAGE ( 20 ). The question of which receptor(s) play a critical role in HNC-BP remains unanswered.…”
Section: Discussionmentioning
confidence: 99%